Efeito da adição de cálcio na formação de inclusões em aços médio teor de carbono desoxidados ao alumínio - Carlos Berlini Filho (2017)
It is necessary to understand the formation of non-metallic inclusions in the technological development of steels with higher quality and a viable production process. Inclusion control is very important to achieve desirable metallurgical and mechanical properties. Continuous Casting performance is deeply affected by inclusions features. This workaimed to carry out experimental and thermodynamic study of inclusion modification during calcium treatment in SAE 1020, SAE 1030 and SAE 1045 aluminum killed steels. The methodology consisted in: a) to produce heats at industrial plant, selected by the amount of aluminum and sulfur; b) to carry out characterization of steel and non-metallicinclusions in samples collected during process on Ladle Furnace, calcium addition station an Continuous Casting; c) a computational thermodynamic study of phase formation by calcium addition. The results obtained by computational thermodynamics showed good agreement with SEM/EDS results. It was possible to establish a correlationbetween aluminum and total oxygen and check the sulfur influence on inclusions formation. The spinel phase fraction decreased after calcium addition and this last was done in excess for some heats. The castability presented a good correlation with area fraction for some phases present on the inclusions